Pancreatic cancer survival trends in the US from 2001 to 2014: a CONCORD‐3 study. Issue 1 (9th November 2022) - Nikšić, Maja; Minicozzi, Pamela; Weir, Hannah K; Zimmerman, Heather; Schymura, Maria J; Rees, Judith R; Coleman, Michel P; Allemani, Claudia; ,
Abstract: Background: Survival from pancreatic cancer is low worldwide. In the US, the 5‐year relative survival has been slightly higher for women, whites and younger patients than for their counterparts, and differences in age and stage at diagnosis [Corrections added Nov 16, 2022, after first online publication: a new affiliation is added to Maja Nikšić] may contribute to this pattern. We aimed to examine trends in survival by race, stage, age and sex for adults (15‐99 years) diagnosed with pancreatic cancer in the US. Methods: This population‐based study included 399, 427 adults registered with pancreatic cancer in 41 US state cancer registries during 2001‐2014, with follow‐up to December 31, 2014. We estimated age‐specific and age‐standardized net survival at 1 and 5 years. Results: Overall, 12.3% of patients were blacks, and 84.2% were whites. About 9.5% of patients were diagnosed with localized disease, but 50.5% were diagnosed at an advanced stage; slightly more among blacks, mainly among men. No substantial changes were seen over time (2001‐2003, 2004‐2008, 2009‐2014). In general, 1‐year net survival was higher in whites than in blacks (26.1% vs . 22.1% during 2001‐2003, 35.1% vs . 31.4% during 2009‐2014). This difference was particularly evident among patients with localized disease (49.6% in whites vs . 44.6% in blacks during 2001‐2003, 60.1% vs . 55.3% during 2009‐2014). The survival gap between blacks and whites with localized disease was persistent at 5 years after diagnosis, and it widened over time (from 24.0% vs . 21.3% during 2001‐2003 to 39.7% vs . 31.0% during 2009‐2014). The survival gap was wider among men than among women. Conclusions: Gaps in 1‐ and 5‐year survival between blacks and whites were persistent throughout 2001‐2014, especially for patients diagnosed with a localized tumor, for which surgery is currently the only treatment modality with the potential for cure.